Imaging flow cytometry reveals the mechanism of equine arteritis virus entry and internalization - Agata Kublicka; Daria Lorek; Agata Mikołajczyk-Martinez; Grzegorz Chodaczek; Aleksandra Chwirot; Barbara Bażanów; Anna Karolina Matczuk (Scientific Reports)
Abstract The process of viral entry into host cells is crucial for the establishment of infection and the determination of viral pathogenicity. A comprehensive understanding of entry pathways is fundamental for the development of novel therapeutic strategies. Standard techniques for investigating viral entry include confocal microscopy and flow cytometry, both of which provide complementary qualitative and quantitative data. Imaging flow cytometry, which integrates the advantages of both methodologies, offers significant potential in virological studies. In this investigation, we employed imaging flow cytometry coupled with immunostaining to monitor the entry of equine arteritis virus EAV into Vero cells via the endosomal trafficking route. Analysis provided an insight into the early infection dynamics across thousands of cells, revealing statistically significant alterations in internalization and uncoating process. Moreover, we evaluated the effectiveness of two inhibitors targeting cellular factors involved in facilitating viral entry: ammonium chloride, which disrupts endocytosis, and camostat mesylate, which inhibits the activity of serine proteases. The results demonstrated a clear distinction between effective and ineffective inhibitors. This study highlighted the potential of imaging flow cytometry to advance the study of viral entry and the evaluation of antiviral agents.